Szczepienia u dzieci z chorobą nowotworową - aktualne polskie zalecenia - Gowin, Ewelina; Januszkiewicz-Lewandowska, Danuta; Jackowska, Teresa; Peregud-Pogorzelski, Jarosław; Wysocki, Jacek (Pediatria Polska - Polish Journal of Paediatrics, 2017)
The article presents, in accordance with current recommendations of the Infectious Diseases Society of America (IDSA) and the Programme of Immunization 2017 (PSO), proposals for the implementation of vaccination in children with cancer, depending on the applied treatment. We recommend to start vaccination 6 months after the end of cancer treatment, which is consistent with the guidelines of the IDSA. After vaccination with a live measles, mumps, rubella (Measles, Mumps, and Rubella, MMR), we recommend antibody level examination. In children treated with anti-CD 20, we recommend vaccination after 6 months after completion of therapy. "Killed" vaccines can be administered 6 months after completion of cancer treatment. In the case of "live" vaccines, time of vaccination must be dependent on dose and time of administration of immunoglobulins. In children with autologous hematopoietic stem cell transplant (HSCT), we recommend vaccination at 6, and after allogeneic at 12 months after the transplant. Children after oncological treatment have an increased risk of viral and bacterial infections, particularly encapsulated bacteria; hence, be aware of vaccination against Haemophilus influenza, Streptococcus pneumoniae and Neisseria meningitidis.